Characterization and Comparative Overview of Complete Sequences of the First Plasmids of Pandoraea across Clinical and Non-clinical Strains - Yong, Delicia; Tee, Kok Keng; Yin, Wai-Fong; Chan, Kok-Gan (Frontiers in Microbiology, 2016)
To date, information on plasmid analysis in Pandoraea spp. is scarce. To address the gap of knowledge on this, the complete sequences of eight plasmids from Pandoraea spp. namely Pandoraea faecigallinarum DSM 23572 (pPF72-1, pPF72-2), Pandoraea oxalativorans DSM 23570 (pPO70-1, pPO70-2, pPO70-3, pPO70-4), Pandoraea vervacti NS15 (pPV15) and Pandoraea apista DSM 16535 (pPA35) were studied for the first time in this study. The information on plasmid sequences in Pandoraea spp. is useful because these plasmid sequences did not match to any known plasmid sequence deposited in public databases. Replication genes were not identified in some plasmids, a situation that has led to the possibility of host interaction involvement. Some plasmids were also void of par genes and intriguingly, repA gene was also not discovered in these plasmids. This further leads to the hypothesis of host-plasmid interaction. Plasmid stabilization/stability protein-encoding genes were observed in some plasmids but were not established for participating in plasmid segregation. Toxin-antitoxin systems MazEF, VapBC, RelBE, YgiT-MqsR, HigBA and ParDE were identified across the plasmids and their presence would improve plasmid maintenance. Conjugation genes were identified portraying the conjugation ability amongst Pandoraea plasmids. Additionally, we found a shared region amongst some of the plasmids that consists of conjugation genes. The identification of genes involved in replication, segregation, toxin-antitoxin systems and conjugation, would aid the design of drugs to prevent the survival or transmission of plasmids carrying pathogenic properties. Additionally, genes conferring virulence and antibiotic resistance were identified among the plasmids. The observed features in the plasmids shed light on the Pandoraea spp. as opportunistic pathogens.